Organic Farming Enhances Diversity and Recruits Beneficial Soil Fungal Groups in Traditional Banana Plantations - Maria Cristina O. Oliveira; Artur Alves; Carla Ragonezi; José G. R. de Freitas; Miguel A. A. Pinheiro De Carvalho (Microorganisms)
This study investigates the impact of organic (OF) and conventional farming (CF) on soil fungal communities in banana monoculture plantations on Madeira Island. We hypothesized that OF promotes beneficial fungal groups over harmful ones, sustaining soil health. Soil samples were collected from six plantations (three OF and three CF) for ITS amplicon sequencing to assess fungal diversity. Results showed that OF significantly enhanced fungal alpha-diversity (Shannon–Wiener index) and Evenness. The phylum Ascomycota dominated OF systems, while Basidiomycota prevailed in CF. Mortierella, a beneficial genus, was abundant in OF and is observed in CF but was less evident, being the genus Trechispora the most well represented in CF agrosystems. Additionally, OF was associated with higher soil pH and Mg levels, which correlated positively with beneficial fungal groups. Functional analysis revealed that OF promoted saprotrophic fungi, crucial for the decomposition of organic matter and nutrient cycling. However, both systems exhibited low levels of arbuscular mycorrhizal fungi, likely due to high phosphorus levels. These findings suggest that organic practices can enhance soil fungal diversity and health, although attention to nutrient management is critical to further improving soil–plant–fungi interactions.